Depositional Models of Deep-Water Gravity-Flow in Lacustrine Basin and Its Petroleum Geological Significance—A Case Study of Chang 6 Oil Group in Heshui Area, Ordos Basin, China - Yang, Yiming; Peng, Jun; Chen, Zhaobing; Zhou, Xiaoying; Zeng, Yao; Wang, Yubin; Wang, Xueying (Frontiers in Earth Science, 2022)
Gravity-flow can carry a large number of sediments and organic matters from shallow water to deep lakes with its strong transporting energy, directly or indirectly facilitating the formation of deep-water tight reservoirs and shale reservoirs. Therefore, studying the genetic types, dynamic mechanisms, and depositional models of gravity-flow deposits is essential in the exploration of unconventional petroleum in large lacustrine basins. This research studied the genetic types, dynamic mechanisms, and sedimentary models of the gravity-flow deposits of the Chang 6 oil group in the Heshui Area, Ordos Basin, China, aiming to reveal its petroleum geological significance. Core observation, microscopic thin section identification, particle size analysis, and determination of rare earth elements were carried out. As a result, three types of gravity-flow deposits are detected, namely, slide-slump, sandy debris flow, and turbidity current. A certain slope gradient in bed form is the necessary geomorphic condition for gravity flow formation, and determines its development level, distribution range, and flow transformation efficiency. Sufficient provenance lays the material foundation and determines its depositional composition and development type. Other factors include earthquakes, volcanoes, and floods, which serve as triggering forces. In addition, fragmentation, liquefaction, and fluid mixing are the main dynamic mechanisms driving flow transformation. Based on the flow type of gravity flow, particle size characteristics, gravity-flow transformation relations, development mechanism, and spatial distribution pattern, we distinguished two depositional gravity-flow models, i.e., slump turbidite body and sublacustrine fan. Re-portrait the spatial distribution of deep-water gravity flow in the study area. From the perspective of sedimentology, explain the genesis of sand bodies in the northeast and southwest. The sandy debris flow in the middle fan braided channel microfacies of the sublacustrine fan sways the development of thick massive sand bodies in the study area. Hybrid event beds formed by the fluid transformation in a slump turbidite are the potential dessert area for deep-water tight oil and gas.